The African National Congress and nationalism in South Africa in light of Manuel Castells' The information age : economy, society and culture, Vol. I, II & III - Cope, Michael Knox (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2007.